How serious are ‘serious non-specific symptoms (SNSS)’? Evaluation of the introduction of a local SNSS pathway, and the pick-up rate of cancers, within this population - Dominic Maxfield; Alexandra Hickey; Temitope Ade-Onojobi; Rohit Sinha; John Painter; Simon Dunn (Clinical Medicine)
Introduction: As part of the NHS Long-Term Plan, ambitions were set that, from 2028, an extra 55,000 people will survive for 5 years or more following cancer diagnosis, through earlier detection. ‘Serious non-specific symptom’ (SNSS) pathways were developed to aid GPs in referring patients with more vague symptoms, concerning for malignancy, that may not already fit into a system specific cancer referral pathway.1Within our Trust, GPs can refer for an urgent computed tomography (CT) chest, abdomen and pelvis, with results reviewed in a weekly multi-disciplinary team (MDT) meeting. Following this, patients are either discharged back to their GP with advice, or referred on to appropriate cancer pathways. Benign disease is also highlighted to GPs, to consider referral to the appropriate specialty if clinically indicated.This audit aimed to look at those patients referred to our local SNSS pathway and evaluate cancer pick up rate, type of cancers and prevalence of benign disease. To date, there are few published data on this within the UK, although one Danish study detected a cancer pick-up rate of 11–20%.2 Materials and Methods: We designed a retrospective audit looking at all patients referred via the SNSS pathway from February 2023 to September 2023 in South Tyneside and Sunderland NHS Foundation Trust. Electronic notes were then reviewed, and we looked at referral indications, inappropriate referrals (those meeting pre-existing suspected cancer pathways), cancer pick-up rate, cancer type and incidence of metastatic disease. Results and Discussion: 502 patients were reviewed, over 30 MDT meetings. This was evenly split between male (45%) and female (55%) patients, with an average age of 71 years. The most common symptom prompting referral was weight loss, in 74.1% of referrals. Of these patients, 7.5% were diagnosed with cancer. Other common symptoms included fatigue (22.5%), abdominal pain (20.7%), anorexia (13.9%) and generalised pain (13.1%).  The overall cancer pick-up rate was 8.6%, with 43 patients found to have a cancer diagnosis.Almost 6% of all patients were inappropriately referred to this pathway, having met criteria for pre-existing cancer pathways. However, even excluding these patients, the overall pick-up rate remained at 8.4%.The most common primary cancers were upper gastrointestinal (25.6%), lung (23.3%) and haematology (11.6%). 37.2% of all patients with cancer had metastatic disease. Benign pathology was detected in 65% of patients.  Conclusion: Overall cancer-pick up rates in our audit suggest that the SNSS pathway has a similar pick-up rate to existing urgent suspected cancer pathways in the NHS (around 7%). This shows that the pathway is valuable in picking up patients with vague symptoms who may not qualify for existing pathways but still have a high incidence of cancer. This provides a valuable tool for GPs to use when they have clinical concern about cancer within non-specific presentations. There are areas for improvement, with 5.6% of inappropriate referrals, potentially highlighting a lack of awareness of pre-existing cancer pathways. We suggest that further national analysis could be done on long-term patient outcomes, and effectiveness of SNSS pathways, including 5-year survival, in such a novel pathway.